1992
DOI: 10.4315/0362-028x-55.9.739
|View full text |Cite
|
Sign up to set email alerts
|

Role of Aerobic Intestinal Pathogens of Fresh Water Fish in Transmission of Human Diseases

Abstract: A total of 101 fresh water fish Tilapia nilotica were bacteriologically investigated for pathogenic and potentially pathogenic organisms. True intestinal pathogens were obtained in 11.8% of the examined specimens including 7.9% with enteropathogenic Escherichia coli and 3.9% with Salmonella species. Serological typing of Salmonella (4 strains) revealed the detection of Salmonella typhimurium (1 strain), S. wangata (2 strains), and S. newport (1 strain). Other potentially pathogenic organisms were isolated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…The localization of Salmonella in fish may differ, and pathogens most frequently were isolated from the alimentary tract (64/150, 41.3 %), compared to other parts of fish-skin (48/150, 32 %) and gills (20/150, 26.7 %) (Hatha and Lakshmanaperumalsamy 1997). Youssef et al (1992) also reported extended survival of Salmonella in the alimentary tract of catfish.…”
Section: Microflora Of Fish and Fish Environmentsmentioning
confidence: 88%
See 1 more Smart Citation
“…The localization of Salmonella in fish may differ, and pathogens most frequently were isolated from the alimentary tract (64/150, 41.3 %), compared to other parts of fish-skin (48/150, 32 %) and gills (20/150, 26.7 %) (Hatha and Lakshmanaperumalsamy 1997). Youssef et al (1992) also reported extended survival of Salmonella in the alimentary tract of catfish.…”
Section: Microflora Of Fish and Fish Environmentsmentioning
confidence: 88%
“…It is generally accepted that bacteria found on fish skin are the same as those found in the contaminated water, including such genera and species as Aeromonas spp. (Aeromonas hydrophila, A. bestiarum, A. caviae, A. jandaei, A. schubertii, A. veronii), Flexibacter spp., Proteus spp., Providencia spp., Psychrobacter spp., Moraxella spp., Pseudomona fluorescens, Acinetobacter johnsonii, Alcaligenes piechaudii, Enterobacter aerogenes, Escherichia coli, Micrococcus luteus, and Vibrio fluvialis (Christensen 1977;Allen et al 1983;Youssef et al 1992;Diler et al 2000;Gonzalez et al 2000Gonzalez et al , 2001Zmyslowska et al 2001).…”
Section: Microflora Of Fish and Fish Environmentsmentioning
confidence: 95%
“…1980; Belchior and Pucci 2000; Davies et al. 2001) or has been occasionally isolated (Youssef et al. 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture, the advent of intensive aquaculture practices led to the outbreak of diseases in all forms of practices ranging from freshwater to marine and warm water to cold water fish (Nicolas, Robic & Ansquer 1989; Youssef, E1‐Timawy & Ahmed 1992; Keskin, Keskin & Rosenrhal 1994; Press & Lillehaug 1995; Karunasagar & Karunasagar 1999). The GI tract is believed to be the major route for the onset of diseases like vibriosis, furunculosis, enteric septicaemia and aeromoniasis in fish.…”
Section: Role Of Gi Microbiota In Disease Outbreakmentioning
confidence: 99%